Enhanced Performance of Flexible ZnO Nanowire Based Room‐Temperature Oxygen Sensors by Piezotronic Effect. (29th May 2013) - Niu, Simiao; Hu, Youfan; Wen, Xiaonan; Zhou, Yusheng; Zhang, Fang; Lin, Long; Wang, Sihong; Wang, Zhong Lin
<x xml:space="preserve">Abstract</x> A flexible oxygen sensor based on individual ZnO nanowires is demonstrated with high sensitivity at room temperature and the influence of the piezotronic effect on the performance of this oxygen sensor is investigated. By applying a tensile strain, the already very high sensitivity due to the Schottky contact and pre‐treatment of UV light is even further enhanced. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>